Acceptance and adoption of open access publishing by researchers in India. Issue 1 (11th January 2019) - Nazim, Mohammad; Zia, Sana
Abstract : Purpose: This paper aims to examine the level of open access (OA) adoption by researchers in Indian Institutes of Technology (IITs), identify predictors of OA status (OA vs non-OA) and explore the availability of OA versions of the articles and venues used by the researches for hosting of their articles. Design/methodology/approach: Articles contributed by the researchers in IITs were searched using an advance search option in the Web of Science Core collection database. The search was restricted to journal articles published in English language in the year 2015. Of the 10, 049 articles retrieved, 1, 023 (10 per cent of the total) were chosen randomly. Articles selected after randomizations were exported to MS Excel for further analyses. Title of each article was searched in Google Scholar to assess its OA availability and venues used by the author for self-archiving. Details of ten articles could not be traced in Google Scholar, and they were excluded from the analysis. Based on the analysis of URLs, all OA articles were classified into three categories: gold OA, green OA and both gold and green OA. The OA articles available through green route were further classified into six categories based on the analysis of the websites and the self-archiving venues used by the authors: institutional repository, subject repository, researcher or scholar's website, organizational website, ResearchGate and other websites. Findings: Of 1, 013 articles examined, OA versions were found for 68.70 per cent of articles. Of the total OA articles, 10.26 per cent articles were available through gold OA and 58.44 per cent were available through green OA, while remaining 6.21 per cent were available via both gold and green OA routes. Although researchers use different venues for self-archiving their articles, ResearchGate and institutional repositories are the most preferred choices by the researchers in IITs. Researchers in IITs are seemed to be unaware of the self-archiving policies of publishers, as more than 85 per cent self-archived articles were found as final PDF versions that are normally not allowed by the publishers. Research limitations/implications: This study is limited to IITs, but it offers theoretical implications for extending its scope to different subjects and institutes. The findings of the study may be useful for the publishers and institutions for formulating OA policies. The findings of the study might be used for raising awareness of OA among researchers and encouraging them to contribute their research outcome in OA outlets. Originality/value: This is the first study in India focusing on the availability of OA research.